The Magellanic Edges Survey I: description and first results - Cullinane, Lara; Mackey, A. D.; Da Costa, G. S.; Koposov, S. E.; Belokurov, V.; Erkal, D.; Koch-Hansen, Andreas; Kunder, A.; Nataf, D. M. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. We present an overview of, and first science results from, the Magellanic Edges Survey (MagES), an ongoing spectroscopic survey mapping the kinematic
Gesehen am 11.11.2020